Assessment of different parameters used in mesh independence studies in two-phase slug flow simulations. (December 2021) - Knotek, Stanislav; Schmelter, Sonja; Olbrich, Marc
Abstract: The paper deals with the influence of grid refinement on the formation and evolution of slugs in numerical simulations of horizontal two-phase flow. For this, six meshes with increasing refinement were used. For a quantitative comparison of the different refinement levels, statistical parameters as well as dominant frequencies were considered. The analysis shows that the sufficient mesh refinement is dependent on the parameter of interest. The mesh independence can be indicated even if further refinement causes earlier slug initiation. Hence, parameters used in a grid studies are suggested to be carefully chosen.